Masalah Pendidikan di Daerah Terpencil dan Relevansi dengan Desain Kurikulum - Dewi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Education in remote areas continues to face various problems that affect the quality and equity of learning outcomes. The lack of adequate facilities and infrastructure, the shortage of competent teachers, and limited access to learning resources are the main obstacles to implementing effective education in these regions. In addition, the national curriculum, which is uniform in nature, is often less relevant to the needs, potential, and local context of the community. This study aims to analyze educational problems in remote areas and their relevance to adaptive and contextual curriculum design. Using a literature review approach, the study shows that a curriculum aligned with local conditions can improve students’ learning motivation, develop regional potential, and strengthen life skills. Therefore, collaborative efforts among the government, educators, and the community are needed to design a curriculum that can effectively address educational challenges in remote areas in a sustainable manner.